2012
DOI: 10.1111/j.1365-2222.2011.03938.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Par j 1/Par j 2 mutant hybrid with reduced allergenicity for immunotherapy of Parietaria allergy

Abstract: Our results demonstrated that a mutant hybrid expressing genetically engineered forms of the major P. judaica allergens displayed reduced allergenicity and retained T cell reactivity for the induction of protective antibodies in vaccination approaches for the treatment of Parietaria pollinosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…However, the Pru p 3 mutant lost the capacity to bind specific IgG antibodies in mice, which could be a problem in the process of a successful immunotherapy [17, 32, 33]. Recently, a hybrid molecule has been characterized as hypoallergenic mutant, and its application in immunotherapy is possible [34]. The two allergenic LTPs from pellitory pollen, Par j 1 and Par j 2, were merged and produced as recombinant proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Pru p 3 mutant lost the capacity to bind specific IgG antibodies in mice, which could be a problem in the process of a successful immunotherapy [17, 32, 33]. Recently, a hybrid molecule has been characterized as hypoallergenic mutant, and its application in immunotherapy is possible [34]. The two allergenic LTPs from pellitory pollen, Par j 1 and Par j 2, were merged and produced as recombinant proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The two allergenic LTPs from pellitory pollen, Par j 1 and Par j 2, were merged and produced as recombinant proteins. The hybrid showed a decrease in its allergenic capacity [34]. …”
Section: Introductionmentioning
confidence: 99%
“…This seems to be particularly important for fragment C, which displays a high prevalence of reactivity in our population (about 80% of the patients). It is important to notice that fragments A and C express non-overlapping regions and contain 3 out of 4 of the highly protruding surface exposed loops (Bonura et al, 2012;Colombo et al, 1998) (loops 1 to 3) identified by the 3D modelling, revealing that both fragments contain immunodominant IgE epitopes.…”
Section: Discussionmentioning
confidence: 97%
“…[2][3][4]. Such drugs which lose their ability to interact with IgE antibodies are considerably safer and can be used at doses several times higher than doses of the standard allergen extracts.…”
Section: Introductionmentioning
confidence: 99%